Planning for success but facing uncertainty: lessons learned from a native oyster, Ostrea lurida, restoration project in the Salish Sea - James T. McArdle; Julie S. Barber; Sarah K. Grossman; Lindy L. Hunter (Frontiers in Marine Science)
Overexploitation and degradation of water quality nearly depleted Olympia oyster stocks in Puget Sound, Washington, USA by the early 1900s. With an intended goal of creating self-sustaining Olympia oyster populations in a target region in Puget Sound, the Swinomish Indian Tribal Community began reestablishing Olympia oysters at two different sites, Kiket and Lone Tree, from 2015-2017. One of our primary objectives was to quantify the biological successes or failures of our reestablished populations. Our results provide a guide for the evolution of project-specific, evidence-based restoration plans that could allow for further use of adaptive management and conservation aquaculture. Following the creation of experimental plots and restoration beds across two sites using 735 m² of shell habitat, including 245 m² of seeded cultch, we measured temporal change in oyster length and density as proxies for growth, recruitment, and survival. Significant growth was observed each year in each lagoon. Despite the known presence of brooding oysters and competent larvae in the region, we found no evidence of recruitment at either site through six years of monitoring. Survival decreased significantly each year and at each site. Thus, while we quantify evidence of growth and reproduction, we are not meeting the success metrics of recruitment or survival therefore hindering the chances of long-term success. We hypothesize that our restoration efforts are hampered by the relatively small population size within our restored areas, insufficient amounts of appropriate surrounding habitat, and lower water residence time. Our study suggests managers need to consistently monitor restoration projects due to site-specific differences and to determine if local failure is a possibility. Low survival and recruitment do not necessitate termination of projects. However, these measurements do suggest that projects like ours need to consider expanding use of conservation aquaculture as a tool or employing adaptive management by developing and implementing novel strategies to increase naturally-occurring adult populations and available habitat.